Analisis Keterkaitan Antar Sektor dan Antar Provinsi dalam Perekonomian Kalimantan Tengah Tahun 2016 (Analisis IO dan IRIO) - Suryani Suryani (Future Science, 2023)
Regional development does not only rely on the contribution of the economic sector in the region to the economy, but also the interaction of a sector with other sectors as well as inter-regional. The demand for goods and services outside the region has led to efforts to increase production so it encourage economic growth. In other words, economic development in one region is expected to trigger economic development in other regions. The purpose of this study is to determine the leading business sectors, the interrelationships between the business sectors, and the economic linkages of Central Kalimantan with other regions in Indonesia. Using the Input-Output Table (I-O) of Central Kalimantan in 2016, this study succeeded in identifying the leading business sectors in Central Kalimantan and the interrelationships between business sectors in Central Kalimantan. In addition, this study also uses the Inter-Regional Input-Output Table (IRIO) to determine economic linkages between Central Kalimantan and several provinces in Indonesia. The results showed that Iron Ore Mining is a leading sector and one of the leading business sectors in Central Kalimantan. In addition, in terms of regional linkages, it was found that changes in final demand in Central Kalimantan will have a major impact on output in DKI Jakarta, East Kalimantan, and South Kalimantan.